RISK FACTOR OF IMPAIRED FASTING GLUCOSE IN PRODUCTIVE AGE GROUP - Abdussalam Abdussalam; Iche Andriyani Liberty; Pariyana Pariyana; Ardesy Melizah Kurniati (Majalah Kedokteran Sriwijaya, 2022)
Impaired fasting blood glucose is a condition that we can still try to turn back to normal. However, this has not been a concern. We aimed to analyze the contribution of risk factors (age, occupation, gender, systolic blood pressure, diastolic blood pressure, body mass index, physical activity, diet quality, and abdominal circumference) to the incidence of impaired fasting blood glucose in people of productive age in Palembang. This research was an observational analytic study with a cross sectional design. The results of the analysis using logistic regression showed that the most dominant risk factor associated with impaired fasting glucose was the diastolic blood pressure with OR=4.56, 95% CI=1.956-10,632, and p-value <0.001. Diastolic blood pressure was a significant and dominant risk factor for impaired fasting glucose in productive age communities. It is recommended that people who are more than 15 years old are expected to maintain blood pressure within the normal range, especially diastolic blood pressure in order to reduce the risk of disrupted fasting blood glucose by continuing to do physical activity